Solar Photovoltaic Thermal Cells Performance Improvement using Jet, Phase Change Material and Nanoparticles Cooling Technology: A review - Mays Shaeli; Monier Baccar; Jalal Jalil (Engineering and Technology Journal, 2024)
The cooling of solar photovoltaic (PV) cells is reviewed in this study. The critical analysis aims to increase PV cell life span and electrical efficiency. To improve the caliber of future studies, this paper examines the implications of earlier studies as well as technical specifics for optimization. Additionally, some of the benefits and drawbacks of various cooling methods are explored. The PV cells cool rate and the PV system's jet impingement cooling technology in PV systems are more effective than any conventional PV cooling systems. Phase change material (PCM) is one of the effective methods used to cool PV cells, as it supporting PV cell cooling in both hot and cold environmental circumstances is beneficial. PCM is appropriate for the cooling application of PV cells due to the requirement of local temperature variation. Many researches and experiences on a different ways of cooling PV collector had been studied to analyze the behavior of PVT systems. Jet and Nanoparticles with PCM are the main ways of cooling and will be discussed in this paper. Lastly, future recommendations based on identified research gaps were suggested. In future work, it is recommended to use jet impingement cooling with PCM together for the PVT system. The proposed system integrates two types of the cooling system with a PV system, the advantage of using jet impingement cooling can result in low average cell temperature for PV cells, and PCM as storage energy with Nanoparticles to enhance the thermal conductive of PCM.